TINJAUAN HUKUM ISLAM TERHADAP JUAL BELI DENGAN SISTEM ONLINE: Studi Kasus di David Navisa Toko (DNT) Store Haurgeulis Indramayu - Sungeb; Irvan Iswandi (Melati Institute, 2023)
DNT stores are stores that provide goods for special customers with quality clothing needs through an online sales system so that they can produce and sell quality and innovative products, by involving more users supported by integrated management systems. The purpose of this thesis are: 1) How is the practice of buying and selling online systems carried out by DNT Store Haurgeulis Indramayu district, 2) How is the application of Islamic law to the buying and selling of online systems conducted by DNT Store Haurgeulis Indramayu. This research uses a qualitative method. The purpose of this survey is to explain the practice of buying and selling carried out by DNT Store Haurgeulis Indramayu and to learn how to discuss Islamic law regarding the practice of buying and selling. The results of this research are DNT stores that have made transactions based on Islamic law because they are in accordance with the terms and conditions of sale and purchase in accordance with the legal terms and conditions. Stores and DNT parties.